Regulated Control of Melanin-Concentrating Hormone Receptor 1 through Posttranslational Modifications - Saito, Yumiko; Hamamoto, Akie; Kobayashi, Yuki (Frontiers in Endocrinology, 2013)
Melanin-concentrating hormone (MCH) is a hypothalamic neuropeptide that plays an important role in feeding behavior. It activates two G-protein-coupled receptors, MCHR1 and MCHR2, of which MCHR1 is the primary regulator of food intake and energy homeostasis in rodents. In mammalian cells transfected with MCHR1, MCH is able to activate multiple signaling pathways including calcium mobilization, extracellular signal-regulated kinase activation, and inhibition of cyclic AMP generation through Gi/o- and Gq-coupled pathways. Further evidence suggests that MCHR1 is regulated through posttranslational modifications, which control its intracellular localization and provide appropriate cellular responses involving G protein signaling. This review summarizes the current data on the control of MCHR1 function through glycosylation and phosphorylation, as related to cell function. Especially, a series of mutagenesis study highlights the importance of complete glycosylation of MCHR1 for efficient trafficking to the plasma membrane.